Buried Treasure? Overlooked and Newly Discovered Evolutionary Contributions to Human Brain Diseases - Diederich, Nico J.; Brüne, Martin; Allen, John S.; Bender, Nicole; Bruner, Emiliano; Changeux, Jean‐Pierre; Cali, Corrado; Dolgova, Olga; Grünewald, Anne; Konopka, Geneviève; Jin, Peng; Lemon, Roger; et al. (John Wiley & Sons, 2026)
Clinical neuroscience focuses on the mechanisms of brain function, but this approach falls short of insights into how the central nervous system (CNS) evolved, both in health and disease. Here, we discuss evolutionary concepts relevant to understanding human brain diseases, on the genetic, subcellular, cellular, connectomic, behavioral, and cultural levels. By revisiting common neurological diseases, we discuss evolved residues from our ancestors, mechanisms of exaptation, antagonistic pleiotropy, and human longevity with the consequent outpacing of biological evolution by cultural evolution. An evolution-based conceptual framework can propel transdisciplinary research targeting the constraints imposed by and compensatory adaptations involved in human-specific neurological diseases.